2000
DOI: 10.1016/s0925-4773(00)00369-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression of mouse netrin-4

Abstract: Netrins are secreted proteins that serve as potent axon guidance molecules in vertebrates and invertebrates. We report the identification of a novel mammalian member of this family. Netrin-4 is similar in predicted size and secondary structure to the other three netrins; all contain, in order, an amino-terminal signal sequence, a laminin-type globular domain of the 'VI' type, three laminin-type epidermal growth factor (EGF) repeats, and a carboxyl-terminal 'netrin module'. In terms of primary sequence, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 19 publications
1
75
1
2
Order By: Relevance
“…S1 A]. Similarity BLAST search analysis of peptides displayed by the enriched phage population showed that the sequence CGLPYSSVC contained a motif embedded within domain IV of the netrin-4 protein (Leu-404-Val-410) (9,10). Detailed sequence alignment revealed that the region mimicked by the peptide motif is not similar to any other known member of the netrin and laminin families of proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 A]. Similarity BLAST search analysis of peptides displayed by the enriched phage population showed that the sequence CGLPYSSVC contained a motif embedded within domain IV of the netrin-4 protein (Leu-404-Val-410) (9,10). Detailed sequence alignment revealed that the region mimicked by the peptide motif is not similar to any other known member of the netrin and laminin families of proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, with critical roles in tissue morphogenesis (2)(3)(4), vascular patterning (5), and angiogenesis (6)(7)(8), netrins have become recognized to mediate functions far beyond axonal guidance. Netrin-4 is expressed in both neural and nonneural tissues (8)(9)(10)(11). In the nervous system, it promotes neurite extension from olfactory bulb (OB) explants but the molecular mechanisms underlying this phenomenon remain unknown.…”
mentioning
confidence: 99%
“…Netrin-1 also was found to be a ligand for integrin a3b1 with the interaction implicated in neuronal migration (Stanco et al 2009). Netrin-4, a more distantly related member with greatest homology with the b-laminin short arm (Yin et al 2000) and widely expressed in basement membranes of developing tissues, has been found to inhibit laminin-111 polymerization, evidence for a binding interaction with the laminin LN domains (Schneiders et al 2007). …”
Section: Other Basement Membrane Componentsmentioning
confidence: 99%
“…129 The biochemical purification of this attractant led to the identification of netrin-1, a laminin related protein, 130 whose function in regulating axon guidance at the midline of the nervous system is conserved in evolution. 3 There are at least three netrin genes in mammals (netrin-1, netrin-3/ NTN2L and netrin-4 [131][132][133][134] ). Netrin-1 can attract several classes of axons throughout the developing nervous system but also acts as a repulsive factor for some axons.…”
Section: Netrins and Their Receptorsmentioning
confidence: 99%